2016
DOI: 10.1097/mpa.0000000000000597
|View full text |Cite
|
Sign up to set email alerts
|

Human Equilibrative Nucleoside Transporter 1 Expression in Endoscopic Ultrasonography-Guided Fine-Needle Aspiration Biopsy Samples Is a Strong Predictor of Clinical Response and Survival in the Patients With Pancreatic Ductal Adenocarcinoma Undergoing Gemcitabine-Based Chemoradiotherapy

Abstract: ObjectivesThis study aimed to clarify whether pretreatment human equilibrative nucleoside transporter (hENT1) expressions in endoscopic ultrasonography-guided fine-needle aspiration biopsy (EUS-FNAB) specimens obtained from resectable, borderline resectable, and locally advanced unresectable pancreatic ductal adenocarcinoma (PDAC) are concordant with those in the resected specimen after gemcitabine-based chemoradiotherapy (Gem-CRT) and to validate the utility of hENT1 expression using EUS-FNAB samples as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…These results were corroborated by in vitro experiments, showing an increased sensitivity to gemcitabine in pancreatic cancer cell lines with high hENT1 gene expression. 92 Yamada et al 93 analyzed pre-treatment hENT1 expression levels in EUS-FNA specimens obtained from patients with different stages of PDAC and compared them to resected specimens after gemcitabine-based chemoradiotherapy. They confirmed that hENT1 expression was an independent prognostic factor in all patients and in the subgroup that underwent resection.…”
Section: Gemcitabine Markersmentioning
confidence: 99%
“…These results were corroborated by in vitro experiments, showing an increased sensitivity to gemcitabine in pancreatic cancer cell lines with high hENT1 gene expression. 92 Yamada et al 93 analyzed pre-treatment hENT1 expression levels in EUS-FNA specimens obtained from patients with different stages of PDAC and compared them to resected specimens after gemcitabine-based chemoradiotherapy. They confirmed that hENT1 expression was an independent prognostic factor in all patients and in the subgroup that underwent resection.…”
Section: Gemcitabine Markersmentioning
confidence: 99%
“…However, the positive predictive values of FNA specimens were relatively high at 71, 80, and 69%, respectively. Yamada et al reported that pretreatment hENT1 expressions in FNA specimens were concordant with those in the resected specimen after GEM-based chemoradiotherapy (32). Further studies are required to confirm the importance of enzyme expression in FNA specimens.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of this concept is the retrospective identification of human equilibrative nucleoside transporter-1 (hENT1) expression as a predictive biomarker in PC patients undergoing gemcitabine-based chemotherapy, in this case primarily obtained through immunohistochemistry and quantitative PCR analysis using previously obtained FFPE surgical samples [ 58 , 95 , 96 ]. Yamada, et al reported high concordance between hENT1 expression in baseline EUS FNA samples compared to subsequent surgical specimens in patients receiving neoadjuvant gemcitabine-based chemo–radiotherapy, and confirmed the role of hENT1 in predicting gemcitabine response [ 97 ]. This supports the clinical utility of EUS FNA biopsy in treatment naïve patients, to evaluate the molecular profile of tumours and identify novel biomarkers both before and during treatment.…”
Section: Clinical Applications Of Molecular Analysismentioning
confidence: 91%